Management of The Academic Achievement Development Program For Elementary School Students - Fitriadi, Rahmad; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Academic achievement development programs are very important to im-prove the quality of student learning optimally so that they are able to achieve higher academic achievement and compete effectively at various levels. The importance of academics for primary school students to build a strong foundation of knowledge, skills, and learning attitudes to support their intellectual and emotional development at the next level of education. The purpose of the research in this article is twofold. 1) Describe the achievement in the competition. 2) Describe the improvement of learning outcomes. The program was created to help students improve their academic grades through a variety of intensive tutoring activities. Methodology: This study uses a qualitative method with a case study approach. Data was collected through observation, in-depth interviews, and documentation. The research participants included principals, teachers, students who par-ticipated in the program. Research shows that the management of the achievement development program at SD Ngarum 1 consists of several main stages, namely planning, implementation, and program evaluation. The program was created to help students improve their academic grades through a variety of intensive tutoring activities. Results: The results of the research, 1) Observing the achievement of student achievement in academic competitions. 2) Describe the improvement of student learning outcomes through academic activities. The program has been shown to have a positive impact on improving students' academic achievement, especially in key subjects such as math and science. The stu-dy found several supporting factors, such as parental support and good learning facilities, as well as inhibiting factors such as lack of human re-sources and time. It is hoped that these findings can help other schools in managing the same program to improve student learning achievement. Applications/Originality/Value: The program has been shown to have a positive impact on improving stu-dents' academic achievement, especially in key subjects such as math and science. The study found several supporting factors, such as parental sup-port and good learning facilities, as well as inhibiting factors such as lack of human resources and time.